2021
DOI: 10.1021/acs.analchem.0c04218
|View full text |Cite
|
Sign up to set email alerts
|

Use of Capillary Zone Electrophoresis Coupled to Electrospray Mass Spectrometry for the Detection and Absolute Quantitation of Peptidoglycan-Derived Peptides in Bacterial Cytoplasmic Extracts

Abstract: Peptidoglycan (PGN) is an essential structure found in the bacterial cell wall. During the bacterial life cycle, PGN continuously undergoes biosynthesis and degradation to ensure bacterial growth and division. The resulting PGN fragments (muropeptides and peptides), which are generated by the bacterial autolytic system, are usually transported into the cytoplasm to be recycled. On the other hand, PGN fragments can act as messenger molecules involved in the bacterial cell wall stress response as in the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…CZE‐ESI‐MS using a 90 cm long, 50/365 μm id/od bare FS capillary, and 100 mM FA as BGE allowed baseline separation and the absolute quantification of peptidoglycan cytoplasmatic peptides (tripeptide‐pentapeptide) in the raw cytoplasmatic extract of bacteria ( Bacillus subtilis ) grown in the presence or absence of a beta‐lactam antibiotic (cephalosporin C) [230]. The absolute quantitation of the tripeptide was based on the [13C, 15N] isotopically labeled standard.…”
Section: Discussionmentioning
confidence: 99%
“…CZE‐ESI‐MS using a 90 cm long, 50/365 μm id/od bare FS capillary, and 100 mM FA as BGE allowed baseline separation and the absolute quantification of peptidoglycan cytoplasmatic peptides (tripeptide‐pentapeptide) in the raw cytoplasmatic extract of bacteria ( Bacillus subtilis ) grown in the presence or absence of a beta‐lactam antibiotic (cephalosporin C) [230]. The absolute quantitation of the tripeptide was based on the [13C, 15N] isotopically labeled standard.…”
Section: Discussionmentioning
confidence: 99%
“…CZE–ESI–MS setup has been applied for the determination of three peptidoglycan‐derived peptides (tri‐, tetra‐, and pentapeptides) and their amidated derivatives in the extracts of bacterial cytoplasma [240]. These peptide fragments are generated by the bacterial autolysis of peptidoglycans—the relevant constituents of the bacterial cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…CZE‐MS/MS has been frequently used for peptidomic studies for disease‐related biomarker discovery, as shown in Section 3.1.3. Besides that, it has also been broadly used for the characterization of peptides in basic research (DeLaney & Li, 2019; Delvaux et al, 2020, 2021; Lamp et al, 2020; Liu et al, 2020; Lombard‐Banek, Yu et al, 2019; Ozawa et al, 2020; Piestansky et al, 2020).…”
Section: Ce‐ms For Multilevel Proteomics Applicationsmentioning
confidence: 99%
“…CZE-MS/MS has been frequently used for peptidomic studies for disease-related biomarker discovery, as shown in Section 3.1.3. Besides that, it has also been broadly used for the characterization of peptides in basic research (DeLaney & Li, 2019;Delvaux et al, 2020Delvaux et al, , 2021Lamp et al, 2020;Liu et al, 2020;Lombard-Banek, Yu et al, 2019;Ozawa et al, 2020;Piestansky et al, 2020). Delvaux et al (2020) employed CZE-ESI-MS for the characterization of cysteine connectivity of disulfide bonds on synthetic and biologically relevant peptides via combinations with ion mobility-MS and theoretical calculations.…”
Section: Peptidomicsmentioning
confidence: 99%